Short-Term Hypothermic Holding of Mouse Immature Testicular Tissue Does Not Alter the Expression of DNA Methyltransferases and Global DNA Methylation Level, Post-Organotypic Culture - Pandya, Riddhi K.; Uppangala, Shubhashree; Salian, Sujith R.; Gupta, Sanjay; Kalthur, Guruprasad; Schlatt, Stefan; Adiga, Satish Kumar (Frontiers in Endocrinology, 2022)
Introduction: Cryopreservation of immature-testicular-tissue (ITT) prior to gonadotoxic treatment, while experimental, is the only recommended option for fertility preservation in prepubertal boys. The handling and manipulation of ITT prior to banking could influence the functionality, genetic and epigenetic integrity of cells. Objectives: To investigate the impact of length of hypothermic holding of mouse ITT on the relative mRNA expression of the DNA methyltransferases (DNMTs) and global DNA methylation, post 14-days of organotypic culture. Methods: ITT from 6-day old mice were handled at hypothermic temperature (4 ℃) for 6 and 24 h prior to 14-days organotypic culture. Relative mRNA expression of Dnmt1, Dnmt3a, and Dnmt3b along with global DNA methylation was measured from the cultured ITT. Results: No significant variation in the expression of Dnmt1, Dnmt3a, and Dnmt3b was observed in relation to varying holding time periods used. Further, global DNA methylation was comparable between 0, 6 and 24 h holding groups. Conclusions: Short-term holding of ITT at 4 ℃ does not affect the DNA methylation process which is reassuring the safety of in vitro approach to derive mature sperm. While fully acknowledging the limitations of this approach in the mouse model, the results we presented in this report will be of significant interest to the field.